Технологічні параметри хліба пшеничного за використання продуктів перероблення гірчиці - Костецька, Катерина Василівна; Ковтун-Водяницька, Світлана Михайлівна; Коломієць, Олександр Вікторович; Kostetska, Kateryna; Kovtun-Vodyanytska, Svitlana; Kolomiiets, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Останніми роками підвищився інтерес до можливості використання побічний продукт виробництва олії. Медою досліджень було оцінити борошно з макухи гірчиці двох видів: білої та сарептської, включивши їх до рецептури хліба пшеничного. Використовували борошно з висушеної макухи, замінивши борошно пшеничне вищого сорту у рецептурі хліба у кількості 3, 5, 10 та 15 %. Зразки хліба вивчали за технологічними характеристики за стандартними методиками. Використання добавок зменшує пористість хліба пшеничного, уповільнює процес бродіння через зниження вмісту клейковини та кислотності тіста та сприяє зростанню показника вологості мякушки. При використанні борошна з гірчиці пористість виробів поступалась контрольному зразку лише на 1–3 %, а кислотність – на 4–11 %. Отже, дослідження властивостей макухи гірчичної шляхом додавання її у вигляді борошна до рецептури хлібобулочних виробів є перспективним. /// EN: In recent years, interest in the possibility of using a by-product of oil production has increased. The aim of the research was to evaluate flour from two types of mustard cake: white and Sarepta, including them in the recipe of wheat bread. Theoretical and practical aspects of technological parameters of wheat products were studied to justify the use of mustard cake in bread baking. Flour from dried cake was used, replacing premium wheat flour in the recipe of bread in the amount of 3, 5, 10 and 15 %. Bread samples were studied for technological characteristics using standard methods. It is worth noting that the technological indicators of experimental samples with the addition of white mustard flour (Sinapis alba L.) had a smaller deviation from the control variant than in samples with mustard flour (Brassica juncea (L.) Czern.). The use of additives reduces the porosity of wheat bread, slows down the fermentation process due to a decrease in the gluten content and acidity of the dough and contributes to an increase in the moisture content of the crumb. When using mustard seeds, the porosity of the products was inferior to the control sample by only 1–3 %, and the acidity – by 4–11 %. The introduction of mustard flour from white and Sarep mustard cake powder in the recipe composition of ordinary wheat dough products in an amount of up to 15 and 10 %, respectively, is optimal, as it will increase its biological value, without significantly reducing its technological characteristics, such as acidity, moisture and porosity of finished products. Therefore, the study of the properties of mustard cake by adding it in the form of flour to the recipe of bakery products is promising. The developed method of producing bread according to new recipes belongs to the food industry and can be used during laboratory baking of bread.
Technological parameters of wheat bread using mustard processing products
Keywords: гірчиця; макуха; борошно пшеничне; рецептура; якість хліба; mustard; seed mea; wheat flour; recipe; quality of bread